Repeated vapor ethanol exposure induces transient histone modifications in the brain that are modified by genotype and brain region - Finegersh, Andrey; Ferguson, Carolyn; Maxwell, Seth; Mazariegos, David; Farrell, Daniel; Homanics, Gregg E. (Frontiers in Molecular Neuroscience, 2015)
Background: Emerging research implicates ethanol (EtOH)-induced epigenetic modifications in regulating gene expression and EtOH consumption. However, consensus on specific epigenetic modifications induced by EtOH has not yet emerged, making it challenging to identify mechanisms and develop targeted treatments. We hypothesized that chronic intermittent EtOH (CIE) induces persistent changes in histone modifications across the cerebral cortex (CCx), nucleus accumbens (NAc), and prefrontal cortex (PFC), and that these histone modifications are altered in a knock-in mouse strain with altered sensitivity to EtOH. Methods: C57BL/6J (B6) mice and α1SHLA knockin mice on a B6 background were exposed to 16 h of vapor EtOH or room air followed by 8 h of room air for 4 consecutive days and sacrificed at multiple time points up to 72 h following exposure. Histone modifications were assessed using Western blot and dot blot. RT-qPCR was used to study expression of chromatin modifying enzymes in NAc and PFC. Results: In NAc, CIE significantly increased acetylation of histone subunit H3 at lysine 9 (H3K9ac) but not lysine 14 (H3K14ac) or lysine 27 (H3K27ac). In PFC, CIE significantly increased H3K9ac but not H3K14 or H3K27ac. There were no significant changes at 8 or 72 h after EtOH exposure in either NAc or PFC. CIE was also associated with increased expression of Kat2b, Kat5, and Tet1 in NAc but not PFC. In CCx, CIE had a significant effect on levels of H3K18ac; there was also a significant effect of the α1SHLA mutation on levels of H3K27me3, H3K14ac, and H3K18ac as well as a trend for H3S10pK14ac. Conclusions: The EtOH-induced histone modifications observed were transient and varied significantly between brain regions. A genetic mutation that altered sensitivity to EtOH was associated with altered induction of histone modifications during CIE. These results have implications for studying EtOH-induced histone modifications and EtOH sensitivity.